Work and home productivity of people living with HIV in Zambia and South Africa. (1st May 2019) - Thomas, Ranjeeta; Friebel, Rocco; Barker, Kerrie; Mwenge, Lawrence; Kanema, Sarah; Vanqa, Nosivuyile; Harper, Abigail; Bell-Mandla, Nomtha; Smith, Peter C.; Floyd, Sian; Bock, Peter; Ayles, Helen; et al.
Abstract : Objective: To compare number of days lost to illness or accessing healthcare for HIV-positive and HIV-negative individuals working in the informal and formal sectors in South Africa and Zambia. Design: As part of the HPTN 071 (PopART) study, data on adults aged 18–44 years were gathered from cross-sectional surveys of random general population samples in 21 communities in Zambia and South Africa. Data on the number of productive days lost in the last 3 months, laboratory-confirmed HIV status, labour force status, age, ethnicity, education, and recreational drug use was collected. Methods: Differences in productive days lost between HIV-negative and HIV-positive individuals ('excess productive days lost') were estimated with negative binomial models, and results disaggregated for HIV-positive individuals after various durations on antiretroviral treatment (ART). Results: From samples of 19 330 respondents in Zambia and 18 004 respondents in South Africa, HIV-positive individuals lost more productive days to illness than HIV-negative individuals in both countries. HIV-positive individuals in Zambia lost 0.74 excess productive days [95% confidence interval (CI) 0.48–1.01; P  < 0.001] to illness over a 3-month period. HIV-positive in South Africa lost 0.13 excess days (95% CI 0.04–0.23; P  = 0.007). In Zambia, those on ART for less than 1 year lost most days, and those not on ART lost fewest days. In South Africa, results disaggregated by treatment duration were not statistically significant. Conclusion: There is a loss of work and home productivity associated with HIV, but it is lower than existing estimates for HIV-positive formal sector workers. The findings support policy makers in building an accurate investment case for HIV interventions. Abstract : Supplemental Digital Content is available in the text